Social workers affecting social policy : an international perspective on policy practice / edited by John Gal and Idit Weiss-Gal. - Gal, John; Weiss, Idit (Policy Press, 2013)
The first book to undertake a cross-national study of social worker engagement in social policy formulation processes, shedding light on policy practice in social work discourse, education and practice in eight liberal democracies.